Determination of the seismicity and peak ground acceleration for Lombok island: an evaluation on tectonic setting - S. Agustawijaya Didi; Sulistiyono Heri; Elhuda Ikhwan (MATEC Web of Conferences, 2018)
Lombok Island is located in the Nusatenggara region, which is considered as one of the most active seismic parts of Indonesia. The determination of seismicity is crucial to the island, since Lombok Island is a relatively dense populated small island. Earthquakes that occurred around the island were generated by southern subduction mega-thrust and northern back-arc thrust. Mostly, distributions are concentrated on the north-west and south-east parts of Lombok Island. Probabilistic data analysis of 309 earthquake events during the period of 1973 - 2017 results in the Gutenberg-Richter parameters (a and b) of 3.62 and-0.53 indicating medium to high seismic activities. The Joyner-Boore attenuation relation seems to be suitable for seismic characteristics of the island. The reconstruction of tectonic setting indicates that the Benioff zone may develop at the depths of 150 km beneath the island causing horizontal tectonic forces working within the direction of N 171 °E - N 351 °E. This could create a strike-slip fault on the crustal basement within the NE - SW direction.